L’engagement affectif dans les tâches de production orale : l’apport du portfolio numérique d’apprentissage et de la vidéo - Paquet, Maxime (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
This article describes the e-portfolio and the video’s contribution to the emotional engagement of high school Quebec students, second cycle, in oral production tasks. A content analysis of self-assessments and individual interviews, as well as data from questionnaires demonstrate that the use of the portfolio and the metacognitive activities that characterize it, support high school students learning by allowing a mindfulness of performance in the oral competency, thus ensuring a better management of the affective scope of the associated tasks. Keywords: e-portfolio, self-recording video, affective engagement, oral production